2014
DOI: 10.5489/cuaj.1483
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics of small renal masses: A prospective analysis from the Renal Cell Carcinoma Consortium of Canada

Abstract: Introduction: Most small renal masses (SRMs) are diagnosed incidentally and have a low malignant potential. As more elderly patients and infirm patients are diagnosed with SRMs, there is an increased interest in active surveillance (AS) with delayed intervention. Patient and tumour characteristics relating to aggressive disease have not been well-studied. The objective was to determine predictors of growth of SRMs treated with AS. Methods: A multicentre prospective phase 2 clinical trial was conducted on 207 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…(18) A further analysis on this cohort of patients revealed that patient age, symptoms at diagnosis, tumour pattern and maximum diameter were not predictors of the growth of SRMs. (25) Finally, Pierorazio during AS (cancer-specific survival 100%), while the overall survival in this group of patients was respectively 96% and 75% at 2 and 5 years compared to 98% and 96% in the active intervention group. (23) Further analysis based on the DISSRM registry has recently shown that patients on active surveillance have a better preservation of renal function assessed by eGFR compared to patients who undergo radical nephrectomy, but not to those who underwent partial nephrectomy.…”
Section: Natural History Of Small Renal Tumorsmentioning
confidence: 94%
“…(18) A further analysis on this cohort of patients revealed that patient age, symptoms at diagnosis, tumour pattern and maximum diameter were not predictors of the growth of SRMs. (25) Finally, Pierorazio during AS (cancer-specific survival 100%), while the overall survival in this group of patients was respectively 96% and 75% at 2 and 5 years compared to 98% and 96% in the active intervention group. (23) Further analysis based on the DISSRM registry has recently shown that patients on active surveillance have a better preservation of renal function assessed by eGFR compared to patients who undergo radical nephrectomy, but not to those who underwent partial nephrectomy.…”
Section: Natural History Of Small Renal Tumorsmentioning
confidence: 94%
“…They showed that none of the evaluated factors (age, symptoms at diagnosis, tumor consistency, and maximum diameter of the mass) significantly predicted tumor growth. After a median follow-up of more than 18 months, the median growth rate was 0.12 cm/y [45].…”
Section: Srms: Growth Risk Of Recurrence and Metastasismentioning
confidence: 98%
“…Notably, no significant clinical or radiological predictors of growth kinetics were found. 60 The predictive role of tumor dimension at the time of presentation has been a matter of debate in literature. In the study by Schiavina et al, the size was not a significant predictor of growth kinetics.…”
Section: Predictive Factors Of Renal Tumor Aggressiveness and Growth mentioning
confidence: 99%